Formulasi dan Uji Aktivitas Antioksidan Serum Spray Gel Minyak Rosemary (Rosmarinus officinalis L.) - Nesa Agistia; Nofriyanti Nofriyanti; Suci Nurhafizah (Fakultas Farmasi Universitas Setia Budi, 2024)
Free radicals can trigger premature aging which can affect the skin structure. Therefore, we need antioxidants that can stabilize reactive free radicals so that they inhibit the free radical oxidation process. One of the plants that can be used as an antioxidant is rosemary (Rosmarinus officinalis L.) in the form of essential oil which contains compounds 1,8-cineole, α-pinene and β-pinene. This study aims to produce a topical preparation of rosemary oil in the form of a serum spray gel and has antioxidant activity. The concentrations of rosemary oil used at F1, F2, F3 and F4 were 0%, 5%, 10%, and 15%, respectively. Evaluation of rosemary oil serum spray gel formulation which includes organoleptic, pH, homogeneity, stickiness, viscosity, stability and spraying pattern. The evaluation results meet the requirements. The conclusion of this study is that rosemary oil serum gel spray preparation is physically stable and the best antioxidant activity is F4 with a rosemary oil concentration of 15% and an IC50 value of 152.6274 µg/mL.